Religious Women in Early Carolingian Francia : A Study of Manuscript Transmission and Monastic Culture - Lifshitz, Felice, 1959- (Book collections on Project MUSE., 2014)
This is a study of the intellectual culture of the women's monasteries of the Main Valley during the eighth century, with a particular focus on Karlburg and Kitzingen. It is based on an analysis of the manuscripts produced and used by the women religious, beginning in the middle decades of the century, when the arrival of the 'Anglo-Saxon missionaries to Germany' (including Boniface of Mainz and his 'beloved', Leoba of Tauberbischofsheim) inaugurated book production in the region. The book also provides many glimpses into non-gendered aspects of monastic culture during the eighth century.